2013
DOI: 10.1111/itor.12062
|View full text |Cite
|
Sign up to set email alerts
|

The locomotive assignment problem: a survey on optimization models

Abstract: The objective of the locomotive assignment problem (LAP) is to assign a fleet of locomotives to a set of trains while satisfying a rich set of operational and budget constraints and optimizing one or more crucial objectives. This paper presents a survey on optimization models for this class of scheduling problems. Depending on the context of application, the kind of model used to solve the LAP varies; accordingly, this influences the solution methodology and algorithms used. In this paper, we review and also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…The locomotive planning problem assigns locomotives to a set of train units in such a way that it minimizes the cost and satisfies a number of business and operational constraints. For a recent survey on the locomotive assignment problem, that also includes variants with some maintenance constraints, see Piu and Speranza (2014). Furthermore, there are many papers about maintenance routing for aviation such as those of Clarke et al (1997), Talluri (1998), and Sarac et al (2006).…”
Section: Maintenance Routingmentioning
confidence: 99%
“…The locomotive planning problem assigns locomotives to a set of train units in such a way that it minimizes the cost and satisfies a number of business and operational constraints. For a recent survey on the locomotive assignment problem, that also includes variants with some maintenance constraints, see Piu and Speranza (2014). Furthermore, there are many papers about maintenance routing for aviation such as those of Clarke et al (1997), Talluri (1998), and Sarac et al (2006).…”
Section: Maintenance Routingmentioning
confidence: 99%
“…The contributions [1,2] give very detailed information about the literature dealing with solving the locomotive assignment problem. In particular, we must mention the works [3,4] and the recent works [5,6].…”
Section: State Of the Artmentioning
confidence: 99%
“…It is obvious that it is not possible to allocate more own locomotives than the transport operator owns to the individual depots. This is ensured by the group of constraints (2). The group of constraints (3) assures that the number of locomotives of the class ∈ that depart from the depot ∈ to serve the connections does not exceed the number of the locomotives found in the depot.…”
Section: Summary Of the Symbols Used In The Mathematicalmentioning
confidence: 99%
“…In the works [3] by Cordeau et al and Piu and Speranza [6] two types of locomotive planning models were identified: Single and Multiple. Single locomotive planning models assume that there is only one type of locomotive available for assignment and train is drived by only one locomotive.…”
Section: Introductionmentioning
confidence: 99%